Association of Visceral Fat Area with Chronic Kidney Disease and Metabolic Syndrome Risk in the General Population: Analysis Using Multi-Frequency Bioimpedance - Seok Hui Kang; Kyu Hyang Cho; Jong Won Park; Kyung Woo Yoon; Jun Young Do (Karger Publishers, 2015)
Background/Aims: Advances in bioimpedance analysis (BIA) technologies now enable visceral fat area (VFA) to be assessed using this method. The aim of this study was to evaluate the clinical relevance and usefulness of VFA as a predictor of chronic kidney disease (CKD) and metabolic syndrome (MS), using BIA. Methods: We identified 24,791 adults who underwent voluntary routine health checkups at Yeungnam University Hospital. In total 22,480 patients were recruited into our study. Participants were divided into 3 tertiles based on their VFA: low, middle, and high tertiles. CKD was defined as an estimated glomerular filtration rate (eGFR) 2. Results: The higher tertile of VFA was associated with a higher prevalence of diabetes mellitus, hypertension, and male sex. Waist-to-hip ratio, body mass index, blood pressure, lean mass, body fat %, and fasting glucose, total cholesterol, triglyceride, GGT, AST, ALT, and uric acid levels all increased as the VFA tertile increased (P P P Conclusion: Our results demonstrated that the VFA, measured by BIA, is a simple method for predicting the risk of CKD and MS.